Neo-adjuvant chemotherapy with cisplatin induces low expression of NMDA receptors and postoperative cognitive impairment. (10th January 2017) - Cheng, Jing; Liu, Xiaoqing; Cao, Longhui; Zhang, Tianhua; Li, Huiting; Lin, Wenqian
Highlights: Preoperative cisplatin treatment might exacerbate postoperative cognition dysfunction. Preoperative cisplatin treatment inhibits the protein expressions of NMDA receptor, PSD-95 and ERK1/2 in the hippocampus. Memantine attenuates alterations induced by cisplatin through up-regulate protein expressions of NMDA receptor, PSD-95 and ERK1/2. Abstract: Whether Neo-adjuvant chemotherapy can affect patients' postoperative brain function is not clear. In this study, we investigated the effect of preoperative cisplatin treatment on postoperative cognitive function and its possible mechanism in rats. Moreover, we also tested whether the NMDAR inhibitor memantine could attenuate cisplatin-induced alterations. 12-month-oldSprague-Dawley rats randomly received an intraperitoneal injection of either cisplatin once a week at a dose of 3 mg/kg for three consecutive weeks or an equivalent volume of normal saline. After the injections, the normal saline injection group was divided into 3 groups (n = 5 each): a normal saline group (group S), normal saline + pentobarbital group (group SP), and normal saline + pentobarbital + operation group (group SPO).The cisplatin injection group was divided into 3 groups: a cisplatin group (group C), cisplatin + pentobarbital group (group CP), and cisplatin + pentobarbital + operation group (group CPO).Rats in the group SP, SPO, CP and CPO were anaesthetized with sodium pentobarbital and then the SPO and CPO groups underwent a simple laparotomy operation. The effects of memantine were tested through two additional groups of rats (cisplatin + memantine group (group CM) and cisplatin + pentobarbital + operation + memantine group (group CPOM)). A Morris water maze test was performed to evaluate the spatial learning and memory ability five days after anesthesia or operation. After the test, the hippocampi were removed for detection of the expression of NMDAR by western bloting. The relevant protein expression levels of PSD95 and ERK1/2 were detected by western blot analysis. Rats treated with cisplatin had a longer mean escape latency and spent a shorter amount of time in the target quadrant than did the normal saline injection rats. Furthermore, the protein expression levels of NMDA receptors, PSD95 and ERK1/2 were decreased in cisplatin group and memantine could up-regulate their expression. These results suggest that neo-adjuvant chemotherapy with cisplatin exacerbate the postoperative cognitive dysfunction in rats, and this may be caused by a lower expression of NMDA receptors in the hippocampus. Memantine could attenuate these alterations.